The Effects of a Mindfulness Program on Mental Health in Students at an Undergraduate Program for Teacher Education: A Randomized Controlled Trial in Real-Life - Juul, Lise; Brorsen, Eva; Gøtzsche, Katinka; Nielsen, Birgitte Lund; Fjorback, Lone Overby (Frontiers in Psychology, 2021)
Background We aimed to investigate the effects of a mindfulness program including Mindfulness-Based Stress Reduction (MBSR) on student teachers´ mental health when offered at their educational institution in a real-life context. Methods A parallel randomized controlled trial (RCT) was conducted among self-selected student teachers at a Danish undergraduate program for teacher education in the autumns of 2019 and 2020. Participation was not recommended in case of 1) clinical depression or a diagnosis of psychosis or schizophrenia, 2) abuse of alcohol, drugs and/or medicine. Randomization was performed by a Statistician who was blinded to the identity of the students. Data was collected using self-reported questionnaires. The primary outcome was change in perceived stress three months from baseline. Secondary outcome measures were symptoms of anxiety and depression, well-being, resilience, mindfulness and thoughts and feelings during rest. The effects were analyzed according to the intention-to-treat principle using mixed-effect linear regression models. Mediating effects via mindfulness skills on the mental health outcomes were explored using structural equation modelling. Results Sixty-seven student teachers were included with 34 allocated to the intervention group (median age: 25 years; female: n=24, 71%); and 33 students (median age: 25 years; female: n=25, 76%) allocated to a waiting list control group. At baseline, mean Perceived Stress Scale scores were 18.88 (SD: 5.75) in the intervention group, and 17.91 (SD: 6.36) in the waiting list control group. A total of 56 students completed the questionnaire at three-month follow-up (28 in both the intervention- and the control group). Statistically significant effects of the intervention were found on perceived stress, symptoms of anxiety and depression, well-being and on three of seven resting state dimensions. No effects were found on resilience or mindfulness. Statistically significant mediated effects via resting state dimensions were found. Conclusion The findings suggest that offering a mindfulness program at an undergraduate program for teacher education can significantly improve the mental health among self-selected students within three months. Results of mediation analysis support the hypothesis that some of the effect may be explained by reduced distracting thoughts.